Long-term survival after resections for pancreatic ductal adenocarcinoma. Single centre study - Lovecek, Martin; Skalicky, Pavel; Klos, Dusan; Bebarova, Linda; Neoral, Cestmir; Ehrmann, Jiri; Zapletalova, Jana; Svebisova, Hana; Vrba, Radek; Stasek, Martin; Yogeswara, Tharani; Havlik, Roman (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
AIM: To analyse the 5-year survival rate of patients undergoing radical surgery for pancreatic ductal adenocarcinoma (PDAC) and to identify prognostic factors. METHODS: A prospectively maintained database of 90 consecutive patients who underwent radical resection for PDAC was analysed. Survival was evaluated using the Kaplan-Meier method. Log-rank test and Cox regression analysis were used for the evaluation of prognostic factors. P values less than 0.05 were considered significant. RESULTS: Mean age (± standard deviation) was 63.2±8.6 years (female 28.9% and male 71.1%). Tumour localisation was in the head in 76 (84.5%), multifocal in 3 (3.3%) and in the body/tail in 11 (12.2%). Pancreatic head resection was performed in 75 (83.3%), total pancreatectomy in 4 (4.4%) and distal pancreatectomy with splenectomy in 11 (12.2%), with standard lymphadenectomy. Venous resection was in 4 (4.4%). Thirty-day and in-hospital mortality occurred in 1 (1.1%), 90-day mortality was 3.3%. On univariate analysis absence of perineural and vascular invasion, stage, absence of lymph node infiltration and no need for transfusion were associated with improved overall survival. On multivariate analysis vascular invasion HR=3.137 (95%CI: 1.692-5.816; P = 0.0003) and postoperative complications HR=2.004 (95%CI: 1.198-3.354; P = 0.008) were identified as significant independent predictors of survival. The five-year survival rate was 18.9%, with five-year recurrence-free survival of 16.7%. CONCLUSION: Vascular invasion and postoperative complications were independent prognostic factors after curative resections of pancreatic cancer in studied cohort.
Keywords: senioři; senioři nad 80 let; reoperace; přežívající; pankreatektomie; Prognosis; Carcinoma, Pancreatic Ductal; complications; pancreatic ductal adenocarcinoma; surgical therapy; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; nádory slinivky břišní; Kaplanův-Meierův odhad; Prospective Studies; Adult; Postoperative Complications; Reoperation; duktální karcinom slinivky břišní; Follow-Up Studies; následné studie; Aged, 80 and over; Pancreatectomy; ženské pohlaví; prognóza; Humans; prospektivní studie; Pancreatic Neoplasms; Survivors; lidé středního věku; dospělí; Female; Aged; long term survival; pooperační komplikace; lidé; Male